The competence to deal critically with online information among economics education students and teacher trainees in economics: implications for teacher training - Nagel, Marie-Theres; Zlatkin-Troitschanskaia, Olga (Empirical Research in Vocational Education and Training, 2025)
Digital media nowadays have become an integral part of teachers’ professional activities. At the same time, studies indicate lacking competences regarding the critical-reflective use of digital media in teachers since the promotion of these competences is not sufficiently implemented in teacher training. In addition, there is a lack of reliable findings on how these competences (also defined as critical online reasoning, COR) develop in prospective teachers at the different stages of teacher training, which constitutes a necessary prerequisite for developing effective training measures. To address this desideratum, the presented study measured prospective economics teachers’ COR competences, and to comparatively examine their levels among teacher trainees and student teachers in different phases of their studies (bachelor’s degree, master’s degree, and post-university practical training phase). For assessing participants’ COR competences, an innovative computer-based performance assessment (CORA) was developed and validated based on the theoretically defined COR construct. In this assessment, the teacher trainees and student teachers were asked to solve open-ended tasks using free Internet research and write short response texts, while also their online behaviour was recorded in situ as Logdata. Subsequently, participants’ CORA performance was scored by trained human raters with a newly developed rating scheme, whereby both the quality of the response texts and the websites used were taken into account. The results reveal few noticeable differences in COR competence levels between the different phases, with master’s students and teacher trainees overall performing better than the bachelor’s students. Regarding the improvement of the competences, a largely continuous increase was observed during the phase of bachelor’s studies, which did not continue into the master’s studies or the practical trainee phase. Also, existing weaknesses in partial sub-skills (e.g. information evaluation) remained mostly the same throughout the different phases of study. These and further results and their implications are discussed in detail in the paper. Overall, the findings underline the need to firmly integrate the COR competences into compulsory studies in all phases of teacher training.